Energy and Sustainability IV 2013
DOI: 10.2495/esus130251
|View full text |Cite
|
Sign up to set email alerts
|

Study on heterogeneous reaction between tar and ash from waste biomass pyrolysis and gasification

Abstract: Fossil energy resources that are available in the world are exhaustible. Therefore, the renewable biomass resource has attracted a lot of attention as the future energy resource. In addition, it is an advantage that the biomass grows while absorbing CO 2 , contributing to the prevention of global warming. Biomass utilization technologies are classified as pyrolysis and gasification, fermentation, and combustion. Fuel gases and synthesis gases produced by the pyrolysis and gasification is used as power generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is worth to develop different technologies for controlling air pollutants emitted from fuel utilization. Some achievements in this study have been applied and linked with other studies reported during the 4th International Conference on Energy and Sustainability [17][18][19].…”
Section: Co 2 Gasifi Cation Reactivity Of Waste Wood Char Samplesmentioning
confidence: 69%
“…It is worth to develop different technologies for controlling air pollutants emitted from fuel utilization. Some achievements in this study have been applied and linked with other studies reported during the 4th International Conference on Energy and Sustainability [17][18][19].…”
Section: Co 2 Gasifi Cation Reactivity Of Waste Wood Char Samplesmentioning
confidence: 69%
“…The condensable products of tar were cooled down and collected in a test tube to measure the yields, and the yields of gas were measured by a gas chromatograph with a fl ame ionization detector (GC-FID) and a gas chromatograph with a thermal conductivity detector (GC-TCD). More detailed results in this study newly added the debate on the contents of the conference paper published in 4th International Conference on Energy and Sustainability [6].…”
Section: Introductionmentioning
confidence: 83%
“…In our experiment, AAEM metal catalysts such as potassium were especially selected since the high catalytic ability of AAEM species in biomass [3][4][5], and iron catalyst was also used because they are inexpensive and readily available. These metal catalysts used in this study, were introduced using an impregnation method to be highly dispersed in the cellulose.…”
Section: Introductionmentioning
confidence: 99%